Sāvitrī’s Journey in the Mahābhārata through the Forest - Umaña Chaves, Alisson (2025)
The article carries out a study focused on the forest as the main landscape found in the substory starring Sāvitrī (Sāvitrī-upākhyāna) located in the Āraṇyaka-parvan. This book develops its narrative in the forest, so it influences the journey made by the princess. The symbolism that this natural landscape carries has been studied over time, it is a recurring theme in literature, so analyzing the forest from the perspective of the journey that the princess makes is essential to understand her development as a wise woman and devoted wife, who tests her knowledge across the worlds.